Diagnosis of benzimidazole resistance in Haemonchus contortus using allele-specific PCR technique - GARG, RAJAT; YADAV, C L (The Indian Journal of Animal Sciences, 2011)
Molecular tools can be of great use in understanding the origin and nature of underlying mechanisms of benzimidazole resistance. In the present study an allele-specific PCR was standardized to diagnose the mutation (Phe to Try) at residue 200 of the isotype 1 beta tubulin gene responsible for benzimidazole resistance in Haemonchus contortus adult and infective larvae. Once standardized, AS-PCR proved to be a powerful tool to detect point mutations at codon 200 of isotype 1 ß-tubulin gene of H. contortus adult worms and infective larvae. The technique can be effectively used for genotyping of benzimidazole susceptible and resistant alleles of H. contortus from sheep.